Optimizing Management of Alfalfa (Medicago sativa L.) Nitrogen Fertilizer Based on Critical Nitrogen Concentration Dilution Curve Model - Yaya Duan; Yi Ling; Haiyan Li; Wenjing Chang; Jiandong Lu; Minhua Yin; Yanxia Kang; Yanlin Ma; Yayu Wang; Guangping Qi; Guoyun Shen (Plants)
The critical nitrogen dilution curve (CNDC) model enables precise nitrogen management by quantifying the threshold of nitrogen deficiency in crops, thereby enhancing both crop productivity and nitrogen use efficiency. However, its applicability to perennial crops remains unclear. In this study, alfalfa (Medicago sativa L.), a perennial leguminous forage, was used as the model crop. Based on two years of field experiments, CNDC models of aboveground biomass were constructed under two nitrogen fertilizer regimes: urea (0, 80, 160, and 240 kg·ha−1, applied in a 6:2:2 basal-to-topdressing ratio) and controlled-release urea (CRU; 0, 80, 160, and 240 kg·ha−1, applied as a single basal dose). Using these models, the nitrogen nutrition index (NNI) and cumulative nitrogen deficit (Nand) models were developed to diagnose alfalfa nitrogen status, and the optimal nitrogen application rates were determined via regression analysis. The results showed that critical nitrogen concentration and aboveground biomass followed a power function relationship under both fertilizer types. For CRU treatments, parameters a and b were 3.41 and 0.20 (first cut), 3.15 and 0.12 (second cut), and 2.24 and 0.40 (third cut), respectively. For urea treatments, a and b were 3.13 and 0.35 (first cut), 2.21 and 0.16 (second cut), and 1.75 and 0.73 (third cut). The normalized root mean square error (n-RMSE) of the models ranged from 3.1% to 13%, indicating high model reliability. Based on the NNI, Nand, and yield response models, the optimal nitrogen application rates were 175.44~181.71 kg·ha−1 for urea and 145.63~153.46 kg·ha−1 for CRU, corresponding to theoretical maximum yields of 14.76~17.40 t·ha−1 and 16.76~20.66 t·ha−1, respectively. Compared to urea, CRU reduced nitrogen input by 18.41~20.47% while achieving equivalent or higher theoretical yields. This study provides a scientific basis for nitrogen status diagnosis and precision nitrogen application in alfalfa cultivation.